Qualidade da aplicação de inseticida em amendoim (arachis hypogaea l.), com e sem adjuvantes na calda, sob chuva simulada - Ferreira, Marcelo da Costa [UNESP]; Lasmar, Olinto [UNESP]; Decaro Junior, Sergio Tadeu [UNESP]; Neves, Samira Scaff [UNESP]; Azevedo, Leticia Henrique de [UNESP] (Univ Federal Uberlandia, 2013)
The present work aimed to evaluate the volumetric distribution profiles, droplet spectra, surface tension, contact angle of droplet and the spraying liquid deposition over the peanut leaves (Arachis hypogaea L.), under artificial rain, in comparison with deposition without rain, using two hydraulic nozzle models of plain fan and insecticide spraying liquids with and without adjuvants addition. It were used a patternator for volumetric distribution analysis, a laser particles analyzer to evaluate droplet spectra produced by SF 110015 and XR 110015 nozzles and tensiometer for droplet tension and contact angle. The spraying liquids evaluated were: water, lambda-cialotrina, lambda-cialotrina + nitrogen fertilizer and lambda-cialotrina + mineral oil. All experiments followed a completely randomized design. Data were submitted to variance analysis by F test and the means comparisons by Scott-Knott test at 5% of probability. According to the results, it must be considered the maximum spacing in spray boom usage of 50 and 90 cm between the nozzles SF110015 and XR110015, respectively. The adjuvants effects on droplet spectra have shown addicted to the nozzle and the product used, and the adjuvants addition to the spraying liquid affected the potential risk of drift; The Volumetric Median Diameter (VMD) of produced droplets by nozzles filled into thin class and were not influenced by the adjuvants. The nitrogen fertilizer adjuvant may be indicated to promote improvements on coverage and droplet deposition on target.

O trabalho objetivou avaliar os perfis de distribuição volumétrica, o diâmetro de gotas, a tensão superficial, o ângulo de contato de gotas e a deposição de calda de pulverização sobre folhas de amendoim (Arachis hypogaea L.) submetidas à chuva artificial, em comparação à deposição sem chuva, usando-se dois modelos de pontas hidráulicas de jatos planos e caldas inseticidas com e sem adição de adjuvantes. Utilizou-se mesa de deposição para análise da distribuição volumétrica, analisador de partículas a laser para avaliar o diâmetro de gotas formadas pelas pontas SF 110015 e XR 110015 e tensiômetro para as análises de tensão e ângulo de contato de gotas. As caldas avaliadas foram: água, lambda-cialotrina, lambda-cialotrina + tributilcitrat + polidimetilsiloxano e lambda-cialotrina + óleo mineral. Os ensaios seguiram um delineamento inteiramente casualizado. Os dados foram submetidos à análise de variância pelo teste F e as comparações das médias pelo teste de Scott-Knott a 5% de probabilidade. Concluiu-se que deve ser considerado um espaçamento máximo na barra de pulverização de 50 e 90 cm entre as pontas, para SF 110015 e XR 110015, respectivamente. O efeito dos adjuvantes no diâmetro de gotas depende da ponta de pulverização e do produto empregado, sendo que a adição dos adjuvantes à calda afetou o risco potencial de deriva; O Diâmetro Mediano Volumétrico (DMV) das gotas produzidas pelas pontas enquadraram-se na classe fina e não foram influenciados pelos adjuvantes. O tributilcitrat + polidimetilsiloxano pode ser indicado para melhorar a cobertura e deposição de gotas no alvo.
Quality of inseticide application on peanut (arachis hypogaea l.) with and without adjuvants in the spraying liquid, under simulated rain
Keywords: Application technology; Pulverization; Thrips; Droplets; Distribution